Towards Efforts and Challenges in Several Significant Protestant Christian Denominations That Obtained Official Recognition By The Vietnamese Government in The Early 21st Century - Ai Khim , Wong (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
In the history of Vietnam, religion served both to integrate the Vietnamese people into a cohesive society and to reinforce its importance of embracing one’s religion, including Protestantism in Vietnam. This paper will concentrate on efforts and challenges in the present day with an understanding of historical roots in several significant Protestant Christian denominations that have been officially recognized by the Vietnamese Government Committee of Religious Affairs (GCRA) in the early 2000s. The Seventh-Day Adventist Church of Vietnam, Vietnam Mennonite Church and Vietnam Baptist Convention (Grace-Southern) were among the eleven officially recognized Protestant Christian denominations from the state government, which have been selected specifically for this study. Qualitative and empirical research were the methods used in this study. The development of Protestantism in Vietnam has been affected by instabilities and uncertainties due to foreign colonization, internal revolutions, global and national wars waged from the mid-19th century into the 20th century, an era known as the “lost period of time” documenting the chronicle history of Protestantism in Vietnam. It is essential to recognize and understand the different periods of history individually, specifically regarding the development of each denomination which has officially obtained recognition by the state government which deserve to be seen as intangible religious and humanity heritage in the history of Vietnam.Received 29th June 2017; Revised 14th April 2018; Accepted 30th April 2018